The Italian Constitutional Court, the plurality of legal orders and supranational fundamental rights: a discussion in terms of interlegality. Issue 3 (September 2022) - Cozzi, Alessia-Ottavia
Abstract: This work aims to investigate the stance of the Italian Constitutional Court (ItCC) on ECHR and CFREU and their respective Courts, ECtHR and CJEU. The aim is to verify if the attitude of the ItCC could be described in terms of openness or closedness, understanding openness as an effort to practise loyal cooperation through procedural means and, substantively, as greater attention for the norms of supranational orders, and closedness as the setting aside of all forms of procedural ties with the supranational Courts and the voluntary dissociation from their outcome, with the purpose of prioritising domestic constitutional provisions. To conduct the analysis, the article refers to the theory of interlegality, questioning whether ItCC, operating 'on the borders between several normative orders', has a broader accountability to these different orders. The first part of the paper is devoted to some elements drawn from the case law indicating openness, such as the language use by the ItCC, the procedures, the legal reasoning, and the effects of judgements. Attention is given to the contextual reference to the recognition norms of both the Italian Constitution and European Union (EU) Treaties and to the increasing use of preliminary rulings to the CJEU. The second part of the paper discusses a substantive criterion created by the ItCC, the 'greatest extension of guarantees', demonstrating that it does not refer to the level of protection of individual rights, but to the balance of the entire constitutional system. Our conclusion is that the ItCC trends concerning supranational rights express a deferent and operational, but vigilant cooperation, retaining a margin to ensure the vitality of the domestic Constitution.